2020
DOI: 10.1186/s13071-020-04310-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of blood-feeding sources in Panstrongylus, Psammolestes, Rhodnius and Triatoma using amplicon-based next-generation sequencing

Abstract: Background Triatomines are hematophagous insects that play an important role as vectors of Trypanosoma cruzi , the causative agent of Chagas disease. These insects have adapted to multiple blood-feeding sources that can affect relevant aspects of their life-cycle and interactions, thereby influencing parasitic transmission dynamics. We conducted a characterization of the feeding sources of individuals from the primary circulating triatomine genera in Colombia using ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 66 publications
3
29
0
Order By: Relevance
“…In agreement with this, a recent study in Colombia conducted an amplicon-based NGS characterization of Triatominae feeding sources (i.e., Panstrongylus, Rhodnius and Triatoma), and found multiple domestic and sylvatic vertebrate feeding sources (including chiropterans) per triatomine [183]. Another study obtained experimental evidence that R. prolixus can feed upon Carollia, Glossophaga, and Desmodus bats, suggesting that frequent transmission of T. cruzi between bats and humans via triatomine vectors is feasible [183,184]. Moreover, many bat species have omnivorous feeding habits and can feed on small mammals and triatomines, which means the probability of infection with T. cruzi could be slightly higher for these animals [183].…”
Section: Bats As Reservoirs Of Trypanosoma Cruzi In the Domestic And Sylvatic Cyclessupporting
confidence: 67%
See 2 more Smart Citations
“…In agreement with this, a recent study in Colombia conducted an amplicon-based NGS characterization of Triatominae feeding sources (i.e., Panstrongylus, Rhodnius and Triatoma), and found multiple domestic and sylvatic vertebrate feeding sources (including chiropterans) per triatomine [183]. Another study obtained experimental evidence that R. prolixus can feed upon Carollia, Glossophaga, and Desmodus bats, suggesting that frequent transmission of T. cruzi between bats and humans via triatomine vectors is feasible [183,184]. Moreover, many bat species have omnivorous feeding habits and can feed on small mammals and triatomines, which means the probability of infection with T. cruzi could be slightly higher for these animals [183].…”
Section: Bats As Reservoirs Of Trypanosoma Cruzi In the Domestic And Sylvatic Cyclessupporting
confidence: 67%
“…Although experimental trials have shown that some triatomine species can have strong preferences for a particular host when given a choice [ 180 , 182 ], subsequent studies have supported a scenario where T. cruzi vectors have adapted to multiple blood-feeding sources, which facilitates its transmission within and between sylvatic and domestic cycles [ 176 , 183 ]. In agreement with this, a recent study in Colombia conducted an amplicon-based NGS characterization of Triatominae feeding sources (i.e., Panstrongylus , Rhodnius and Triatoma ), and found multiple domestic and sylvatic vertebrate feeding sources (including chiropterans) per triatomine [ 183 ]. Another study obtained experimental evidence that R. prolixus can feed upon Carollia , Glossophaga , and Desmodus bats, suggesting that frequent transmission of T. cruzi between bats and humans via triatomine vectors is feasible [ 183 , 184 ].…”
Section: Epidemiology and Evolution Of Bat Trypanosomes In A One Health Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Because in samples from feces mixed infections are common ( 8 , 83 , 84 ), it is important to deploy NGS tools in studies of Blastocystis subtype diversity to have a better picture of STs present within a host. The usefulness of NGS in detecting mixed infections has also been demonstrated in other organisms such as Trypanosoma cruzi and Trypanosoma rangeli where NGS successfully detected co-infections of these two parasites in infected triatomines ( 85 ) and in triatomine food sources ( 86 ). NGS has aided in the determination of the diversity of low-density Plasmodium falciparum infections ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…This method of metabarcoding and deep sequencing would be advantageous given soft tick biology, including multiple bloodmeals obtained during immature development and multiple gonotropic cycles of adults. The amplicon deep sequencing approach would allow the ID of not just the most recent bloodmeal but also the potential to detect prior vertebrate bloodmeals ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%